Effect of unintentional boosting on exercise performance in a tetraplegic athlete - Gee, C. M.; Lacroix, M. A.; West, C. R. (Medicine & Science in Sports & Exercise, 2018)
Boosting is the induction of autonomic dysreflexia (AD) to reflexively activate otherwise dormant thoracolumbar sympathetic circuitry to "boost" the capacity of the cardiovascular system and enhance exercise performance. AD is a life-threatening condition unique to individuals with spinal cord injury (SCI) characterized by a sudden increase in sympathetic activity below the level of the SCI. Here we report on the temporal HR response to an episode of unintentional boosting during a validated field-based exercise performance test in an athlete with tetraplegia.